2013
DOI: 10.4088/jcp.12m08278
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind, Placebo-Controlled, Pilot Trial of Paliperidone Augmentation in Serotonin Reuptake Inhibitor–Resistant Obsessive-Compulsive Disorder

Abstract: ClinicalTrials.gov identifier: NCT00632229.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 0 publications
0
27
1
1
Order By: Relevance
“…The results of the individual atypical anti-psychotics were as follows: (a) Risperidone: Five studies were identified [12,[14][15][16][17] with 77 participants in total taking risperidone and 89 receiving placebo. The overall difference was statistically significant with an overall mean reduction of 3.89 points on the Y-BOCS (95% CI = 1.43-5.48) and an effect size of D = 0.53 ( Figure 2).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the individual atypical anti-psychotics were as follows: (a) Risperidone: Five studies were identified [12,[14][15][16][17] with 77 participants in total taking risperidone and 89 receiving placebo. The overall difference was statistically significant with an overall mean reduction of 3.89 points on the Y-BOCS (95% CI = 1.43-5.48) and an effect size of D = 0.53 ( Figure 2).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…All the studies used different definitions of recovery of either >25% [14,16] or >35% [12,15,17] reduction in Y-BOCS outcome either with or without additional criteria such as change on Clinical Global Improvement scale [12,15]. We therefore confined our categorical analysis to risperidone studies only since the previous Cochrane review [4] had conducted this analysis on other antipsychotics and there were no new studies for quietapine and olanzapine.…”
Section: Data Itemmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otra parte, según estudios no controlados, el amisulpride puede ser útil para potenciar el tratamiento del TOC resistente a ISRS (28,29) y un estudio piloto controlado con placebo mostró una tendencia no significativa a favor de la paliperidona como coadyuvante en el tratamiento de TOC resistente a ISRS (30). Por último, hay reportes de casos (31,32) y un estudio no controlado (33) que sugieren utilidad de la ziprasidona en TOC resistente.…”
Section: Rev Neuropsiquiatr 79 (4) 2016unclassified
“…No RCTs exist that have examined the efficacy of ziprasidone. Of the newer atypical antipsychotic drugs asenapine, lurasidone, iloperidone, and paliperidone, only paliperidone has been examined in a double-blind, placebo-controlled trial, with a nonsignificant trend toward improvement in OCD symptoms (130).…”
Section: Ocd Refractory To Initial Pharmacological Managementmentioning
confidence: 99%